Evaluation of Vanadium Influence in AlSi10MgMn Alloy with Increased Iron Level - Zihalova, Maria; Bolibruchova, Dana (Manufacturing Technology Journal, 2016)
Final properties of castings made of aluminium alloys strongly depend on amount of impurities. Production of high quality parts thus requires strict control of impurity level or elimination of detrimental effects caused by presence of impurities. Such requirements are even more important in case of castings made of recycled materials. In Al-Si based alloys is very important awareness of the problems with the presence of iron as an impurity. Negative iron effect is expressive even in low amounts, and with higher level becomes more harmful. Elimination of its effects can be performed by several techniques, from which no one have general implementation. One of the possible ways is addition of so called iron correctors to the alloys. Influence of vanadium as iron corrector is still not precisely examined. In this article, influence of vanadium to AlSi10MgMn alloy with 1.0 wt. % of iron is analysed by tensile and hardness testing together with microstructural evaluation.
Keywords: AlSi10MgMn alloy; Intermetallic phase; Correctors of iron; Vanadium